2017
DOI: 10.3126/hjsa.v7i0.17149
|View full text |Cite
|
Sign up to set email alerts
|

Social Accountability for Adolescent Sexual and Reproductive Health

Abstract: Adolescent population of Nepal is facing health and social problems related to sexual, reproductive, behavioral and traditional social practices. Adolescent pregnancy, child marriage, unwanted pregnancies, Chhaupadhi (restrictions during menstruation and delivery), sexual-gender based violence, unsafe abortion, HIV/AIDS, drug addiction and suicide are major problems which have severe consequences in the lives of adolescents in Nepal. Addressing such daunting problems that adolescents are facing today needs hol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Previous study findings also suggest that the lack of a well-designed and well-implemented social accountability approach makes services less appropriate for service users. 51 Thus, using social accountability strategy may be a promising strategy for improving access and utilization of SRH services. 52 , 53 The finding implies that there is a gap between the implementation of strategies and what is happening in practice.…”
Section: Discussionmentioning
confidence: 99%
“…Previous study findings also suggest that the lack of a well-designed and well-implemented social accountability approach makes services less appropriate for service users. 51 Thus, using social accountability strategy may be a promising strategy for improving access and utilization of SRH services. 52 , 53 The finding implies that there is a gap between the implementation of strategies and what is happening in practice.…”
Section: Discussionmentioning
confidence: 99%
“…•Increased willingness to dialogue in public on FP [ 14 ] and SRHR problems faced by adolescents [ 17 ]…”
Section: Appendixmentioning
confidence: 99%
“…A 2016 review exploring activities that explicitly engage community members to improve RMNCAH found very little and poor-quality evidence for effects on family planning or birth spacing outcomes [12]. There are recent studies (Appendix) focusing on family planning and contraceptive services that reported positive outcomes, such as improvements in service quality, financial allocation for contraceptive service provision [13,14], and community awareness [15][16][17] and participation [13,14]. Studies have also reported increases in the current use of modern contraceptives [18] and the acceptability of providing family planning to adolescents [19].…”
Section: Introductionmentioning
confidence: 99%